Functional studies of insecticides and acaricides acting on ligand-gated ion channels - Iqbal, Sofia (2019)
Arthropod pests such as ticks and fleas are important ectoparasites of livestock and companion animals that cause economic losses, spread disease and pose a public health risk. They are most commonly controlled using chemical pesticides, the majority of which have a neurotoxic mode of action. Two important targets within the arthropod nervous system are the GABA receptor (GABAR) and the nicotinic acetylcholine receptor (nAChR). They are targeted by a diverse range of chemical classes, although prolonged use of certain compounds has resulted in the development of resistance. This continues to be an ever-increasing problem for effective pest control and is often caused by simple point mutations within the target that disrupt the high selectivity of the target-ligand interaction at the binding site.